Malaysian Muslim Counsellors’ Perceptions on Value-Neutral Stance and Religious Values in Counseling Practice A Preliminary Study - Md. Yusoff., Yusmini (Jurnal Usuluddin, 2014)
Malaysian Counseling practices had its history from Euro-American Counseling models which emphasise the practice of objective and valueneutral stance. Within these models, counsellors conceptual and theoretical understandings of Counseling were strongly shaped and developed. Therefore, this preliminary study draws on this history and questions the effects of this stance in Malaysian Counseling practices particularly in working with religious and spiritual values.